KEJAHATAN SIBER DAN PENIPUAN KOMPUTER: APA PENCEGAHAN YANG DAPAT DILAKUKAN? - Birlin, Raisa aqila; Lisa Oktaviani; Maninggor Esteria Silaban; Aryan Danil Mirza BR (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
A The fast development of technology has brought both positive and negative effects, incluiding an increase in cybercrime like computer fraud. Cybercrime involves illegal actions through computer networks, such as data theft and online scams, whic harm individuals, organizations, and goverments. Data from e-MP Robinospal Bareskrim Polri (2022) shows that cybercrime cases are on the rise, with criminals becoming more skilled at exploiting systems. Computer fraud uses technology to gain illegal profits through methods like phising and ransomware. The losses from cybercrime are significant, affecting both finances and reputation. Therefore, preventive measures are important at all levels, from indivuduals to organizations. This article takes a qualitative approach, using a literature review to explore tge issue of cybercrime and computer fraud, along with strategies for prevention. Key actions include implementing security protocols, improving digital literacy, and encouraging collaboration among different parties to reduce the negative effects of cybercrime and protect information security.